Model Penyelenggaraan Berbasis Mutu Program Pascasarjana Magister Terapan Transportasi di Politeknik Ilmu Pelayaran Semarang - Antoni Arif Priadi; Dian Wahdiana; Nila Mutia (Politeknik Ilmu Pelayaran Semarang, 2022)
The purpose of this study is to describe the implementation model of the Master of Applied Transportation program. The applied master program chosen and modeled is the PIP Semarang with the consideration that there is no special Applied Master Study Program that is directly related to the shipping industry held in Indonesia. In addition, from the results of the needs analysis, the results state that there are more than 90% of graduates who have not received information related to the Master's study program which is linear with the study program they have taken and the relationship with the current scope of work proves the need to open a Master of Transportation Applied Study Program at PIP Semarang. This study uses a combined method (mixed method). Quantitative data were obtained by filling out questionnaires by 539 respondents, of which 28% of respondents were civil servants including teachers and lecturers, 25% of respondents were private employees. As a deepening of the results obtained from the questionnaire, a quantitative descriptive analysis was carried out using the PIP Semarang education management documents. The results showed that 57% of respondents stated the need for maritime specificity in the implementation of the applied master's education program in transportation. This research concludes that PIP Semarang has fulfilled the readiness of the required resources for the development of the Applied Masters study program which includes 8 National Education Standards.